Isolation, characterisation and evaluation of PINI and BP genes in ralation to inflorescence architecture in black pepper (Piper nigrum L.) - Smitha Bhasi (Department of Plant Biotechnology College of Agriculture, 2019)
The study entitled “Isolation, characterisation and evaluation of PIN1 and BP genes in relation to inflorescence architecture in black pepper (Piper nigrum L.)” was conducted during 2015-2018 at the Department of Plant Biotechnology, College of Agriculture, Vellayani, Thiruvananthapuram. The objective of the study was to isolate and characterize PIN1 (PINFORMED1) and BP (BREVIPEDICELLUS) genes in black pepper and to evaluate the role of these genes in branching of spikes by studying their differential expression pattern in branching and non-branching varieties of black pepper. Spike samples at their three developmental stages viz. stage-1 (12-15 days after emergence of bud; 1-2 cm length), stage-2 (22-25 days after emergence; 6-8 cm length) and stage-3 (32-35 days after emergence; 9-12 cm length) were collected from bush pepper plants of branching type (Thekken) and non- branching varieties (Panniyur-1, Karimunda and Aimpiriyan) and used for the study. Morphological, histological, molecular (genome, transcriptome and proteome levels) and hormonal analyses were carried out. On morphological analysis of spike characteristics based on IPGRI descriptors, Thekken exhibited six fold increase in number of berries per spike (480) compared to Panniyur-1 (79). Maximum spike length (14 cm) was exhibited by Panniyur-1, and minimum by Karimunda (7.5 cm). Thousand berry weight was maximum for Aimpiriyan (135.6 g) and minimum for Thekken (100 g). Microscopic analysis showed the presence of thick fleshy bracts in Thekken compared to Panniyur-1. Spikelet emergence was noticed at stage-3 in the spikes of Thekken. Histological analysis revealed the presence of a distinct mass of meristematic tissue in stage-1 of Thekken that gradually differentiated during stage-2 and emerged into a spikelet during stage-3. For genome level analysis, DNA isolated by CTAB method was amplified by Polymerase Chain Reaction (PCR) with gene specific primers for PIN1 and BP, designed using Primer-3 software. Two amplicons of size 124 bp and 650 bp were obtained using PIN1 specific primer. Sequence of the 124 bp amplicon on BLASTn analysis revealed 94% identity to PIN1 gene of Canna sp. while the 650 bp amplicon revealed 83% identity to auxin efflux carrier gene of Sorghum bicolor. Amplification of the genomic DNA with primer designed for BP gene produced an amplicon of 145 bp size and its sequence revealed 88% identity to homeobox protein knotted-1 like gene family to which BP belongs. Twenty five per cent variation was noticed between the PIN1 sequences of Thekken and Panniyur-1, whereas only five percent variation could be noticed between BP sequences. For transcriptome level analysis, cDNA reverse transcribed from total RNA isolated using Trizol method was used. Differential expression analysis was carried out using Real Time PCR. The expression pattern of PIN1 was similar in both Thekken and Panniyur-1. However, the expression levels were significantly higher in all stages of Thekken with maximum (14 fold) at stage-1. The expression pattern of BP varied in Thekken compared to Panniyur-1. It showed twenty seven fold over expression in stage-1 and three fold down regulation in stage-2 of Thekken compared to Panniyur-1. Rapid Amplification of cDNA Ends (RACE) of the 124 bp amplicon of PIN1 generated two fragments of size 280 bp and 580 bp. Protein domain analysis of the fragments revealed the presence of zinc finger domains. Proteome analysis using SDS Polyacrylamide gel electrophoresis (PAGE) showed unique protein fragments in all the stages of inflorescence in Thekken (100 KDa fragment in stage-1 and stage-2; 48 KDa and 55 KDa fragments in stage-3). Hormonal analysis of auxin using High Performance Liquid Chromatography (HPLC) revealed that IAA content in Thekken (25 ppb) was one-fourth compared to Panniyur-1 (90 ppb) and one-third compared to Karimunda (60 ppb). Enzyme Linked Immuno Sorbant Assay (ELISA) showed an increase in total cytokinin content in Thekken from stage-1 (2.8 ng/g) to stage-2 (3.5 ng/g), in contrast to non-branching varieties (3.6 ng/g to 3.0 ng/g). The present study is the first report on the isolation and characterisation of coding sequences of PIN1 and BP genes in black pepper. The fragments of PIN1 and BP genes isolated were deposited in the NCBI database. The 580 bp PIN1 sequence revealed numerous zinc finger domains similar to PIN1 gene of Arabidopsis indicating similar function. PIN1, being an auxin efflux carrier, its overexpression noticed in Thekken at the transcriptome level correlated with the lower auxin content in the hormonal analysis. The twenty seven fold expression of BP noticed in Thekken correlated with the increase in cytokinin content and the emergence of a differentiated meristamatic tissue that was prominent in the histological sections of stage-2 of Thekken. The unique proteins of sizes 100 KDa, 48 KDa and 55 KDa in Thekken in proteome analysis suggest the presence of novel proteins in Thekken. The differential expression of PIN1 and BP genes revealed in the present study indicates the significant role of these genes in inducing the spike branching trait in Thekken.